Effectiveness of Implementing the Teams Games Tournament (TGT) Learning Model on the Communication Ability Students - Maghfira, Salma Nuril; Khikmah, Nur (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research aims to determine the effectiveness of implementing the Teams Games Tournament (TGT) model on students' communication skills. This research is a type of quasi-experimental quantitative research. This research design uses a post-test only control group design. The subjects of this research were students in classes IV A and IV B at MI Miftahul Huda Tayu, totaling 26 students in each class, taken using the Simple Random Sampling technique. The data collection technique uses interviews and non-test methods in the form of questionnaires. The data in this research was obtained through primary data and secondary data. Primary data in this research is in the form of interviews with class teachers and data in the form of student communication skills questionnaire results, which are analyzed using the t-test. Secondary data in this research consists of all information from reference books and scientific journals. Based on the t-test calculation, it is obtained -1.686 < t count < 1.686 and t count = -8.45, so it can be seen that the t count is not between the values -1686 to 1.686. Apart from that, this is reinforced by the results of hypothesis testing with the t-test. The results of the post-test t-test obtained Sig results. (2-tailed) 0.008 < 0.05, which means there is a difference in post-test results between the experimental class and the control class. It can be seen that H0 is rejected, so it can be concluded that this means the Teams Games Tournament (TGT) learning model is effective for students' communication.